Advances in the Research on Brown Carbon Aerosols: Its Concentrations, Radiative Forcing, and Effects on Climate - Shuai Li; Hua Zhang; Zhili Wang; Yonghang Chen (Aerosol and Air Quality Research)
Abstract Brown carbon (BrC) are important light-absorbing carbonaceous aerosols in the atmosphere, and it is of great significance to study the climate effects of BrC for regional or global climate change. This paper reviews recent advances in research on the radiative forcing of BrC, its effects on temperature and precipitation, and snow/ice albedo. Recent research suggests that: (1) Climate effects of aerosols can be represented more accurately when including BrC absorption in climate models; the regions with the highest global mean surface BrC concentrations estimated by models are mostly Southeast Asia and South America (biomass burning), East Asia and northeast India (biofuel burning), and Europe and North America (secondary sources); estimates of BrC radiative forcing are quite erratic, with a range of around 0.03–0.57 W m−2. (2) BrC heating lead to tropical expansion and a reduction in deep convective mass fluxes in the upper troposphere; cloud fraction and cloud type have a substantial impact on the heating rate estimates of BrC. The inclusion of BrC in the model results in a clear shift in the cloud fraction, liquid water path, precipitation, and surface flux. BrC heating decreases precipitation on a global scale, particularly in tropical regions with high convective and precipitation intensity, but different in some regions. (3) Uncertain optical properties of BrC, mixing ratio of radiation-absorbing aerosols in snow, snow grain size and snow coverage lead to higher uncertainties and lower confidence in the simulated distribution and radiative forcing of BrC in snow than BC. To reduce the uncertainty of its climate effects, future research should focus on improving model research, creating reliable BrC emission inventories, and taking into account the photobleaching and lense effects of BrC.